Design and Construction of a Web Application for Recording Vehicle Services with Schedule Notification Features and Component Lifetime Estimation - Winda Hafiza; Afif Badawi; Barany Fachri (Bahasa Indonesia, 2026)
Vehicle maintenance is an important activity to maintain vehicle performance and extend the lifespan of vehicle components. However, many vehicle owners still record maintenance activities manually, causing difficulties in monitoring service schedules and determining the appropriate time for component replacement. This study aims to design and develop a web-based vehicle service recording application equipped with service schedule notification and component lifespan estimation features. The system was developed using the waterfall software development method and implemented using PHP and MySQL. The application provides vehicle data management, component lifespan estimation, and service report generation. System testing was conducted using the Black Box Testing method. The results indicate that all application features function properly according to user requirements. The developed application can assist users in recording vehicle service history, monitoring maintenance schedules, and estimating component replacement periods effectively and efficiently.